Histopathology of infection and colonization of Quercus ilex fine roots by Phytophthora cinnamomi - Ruiz Gómez, F. J.; NAVARRO-CERRILLO, R. M.; Sánchez-Cuesta, R.; Pérez-de-Luque, A. (Plant Pathology, 2014)
Quercus ilex is one of the European forest species most susceptible to root rot caused by the oomycete Phytophthora cinnamomi. This disease contributes to holm oak decline, a particularly serious problem in the ‘dehesas’ ecosystem of the southwestern Iberian Peninsula. This work describes the host–pathogen interaction of Q. ilex and P. cinnamomi, using new infection indices at the tissue level. Fine roots of 6-month-old saplings inoculated with P. cinnamomi were examined by light microscopy and a random pool of images was analysed in order to calculate different indices based on the measured area of pathogen structures. In the early stages of invasion, P. cinnamomi colonizes the apoplast and penetrates cortical cells with somatic structures. On reaching the parenchymatous tissues of the central cylinder, the pathogen develops different reproductive and survival structures inside the cells and then expands through the vascular system of the root. Some host responses were identified, such as cell wall thickening, accumulation of phenolic compounds in the middle lamella of sclerenchyma tissues, and mucilage secretion blocking vascular cells. New insights into the behaviour of P. cinnamomi inside fine roots are described. Host responses fail due to rapid expansion of the pathogen and a change in its behaviour from biotrophic to necrotrophic.
Keywords: histopathology; infection index; main factors responsible for; Oak decline; phytophthora cinnamomi; Quercus ilex; root rot; s